An Overview on Pharmacological Effects of Few Phytopolyphenols from Dietary and Herbal Origins - Bharti Ahirwar; Dheeraj K. Ahirwar; S. K. Lanjhiyana; Sanmati K. Jain (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
The objective of the present chapter is to highlight the immunomodulation, antioxidant, anticancer, anti-inflammatory, antibacterial, and antiviral properties of phenolic compounds. Various research studies authenticated that these phytopolyphenols cause lesser side effects and toxicity in comparison to synthetic or chemical drugs of modern days in human subjects. These polyphenols were used in the form of dietary food, plant extracts, or active phytoconstituents compounds respectively. Today’s world populations were directly or indirectly dependent on these polyphenols in the form of dietary or herbal medicines due to resultant healthcare benefits. The present chapter included a few types of polyphenols viz., flavonoids, lignans, phenolic acids and their analogs, tannins, quinines, etc. for the reasons of possible biological activities in human bodies.